The Effectiveness of Using the Hello English Application to Improve Vocabulary Development on Descriptive Text - Sari, Meisy Dwi Intan; Daud, Afrianto; Masyhur (IKIP Siliwangi, 2025)
This study explores the effectiveness of using the Hello English application to improve vocabulary development on descriptive text of the tenth-grade students of SMAN 5 Pekanbaru. The research method used was a pre-experiment research design with pre-test and post-test one group. A total of 38 students of class X.3 became the sample of this study. Data was collected through a multiple-choice questions test with as many as 30 items. The results showed that Ha was accepted and H0 was rejected because the students' average score increased significantly from the pre-test to the post-test after treatment using the Hello English application. This can be seen from the mean score of the pre-test results which was 73.11 while the mean score of the post-test amounted to 92.16. With interesting features involving vocabulary exercises, educational games, and quizzes, the application can increase students' motivation to learn English. This application is also very useful for students especially in learning vocabulary and practicing it through descriptive text. For teachers, this application can help the learning process with different methods. The findings conclude that the use of technology-based applications such as Hello English can be an effective alternative in teaching English, especially in vocabulary development.